Determinan Berat Badan Lahir Rendah di 34 Provinsi Indonesia Tahun 2019-2022 - -, Mohammad Noval (Brida Provinsi Jambi, 2025)
The degree of public health in a country can be reflected in the infant mortality rate. In Indonesia, infant deaths, especially during the neonatal period, are the highest cause of Low Birth Weight (LBW), which also affects the quality of human resources itself and risks a slowdown in the country's economic growth. The study aims to see whether smoking, prenatal coverage, supplementary feeding, childbirth in health facilities, and the risk age of pregnant women <20 and >35 years have a significant heve probability chance of Low Birth Weight (LBW) incidence in Indonesia in 2019-2022. The research data used is secondary data derived from BPS RI and Kemenkes RI reports using logistical regression analysis methods. The results obtained were smoking consumption, prenatal services, and supplementary feeding are non-significant have probability, as well as childbirth in health facilities and pregnancy age of mothers at risk <20 years and >35 years of significant have probability chances against BBLR in 34 Indonesian provinces in 2019-2022.